The systematic status of amblyphrynus ingeri (amphibia: leptodactylidae) with the description of an allied species in western colombia (1981)
Amblyphrynus ingeri is known from three specimens, all collected on the Cordillera Oriental of Colombia. New material reveals that Amblyphrynus is inseparable from the sulcatus group of Eleutberodactylus. The sulcatus group contains five species: E. helonotus, E. ingeri, E. maussi, E. sulcatus, and a new species described herein on the basis of specimens from the CordillerasCentral and Occidental. The new species and E. ingeri are the mostderived members of the species group and form a tight cluster with E. sulcatus, an Amazonian species.